Oxford international primary Science 5 - Roberts,Deborah; Terry Hudson; Alan Haigh; Geraldine Shaw (Karachi: Oxford university press, 2023)
"Oxford International Primary Science 5" is an educational resource designed to engage primary school students with fundamental scientific concepts through an inquiry-based approach. The book covers essential themes such as life sciences, physical sciences, and Earth sciences, encouraging hands-on exploration and experimentation. With a focus on critical thinking and problem-solving, it empowers students to ask questions, conduct investigations, and analyze results. The resource features colorful illustrations and real-world examples to make science relatable and enjoyable. Additionally, it provides teachers with lesson plans and assessment tools to facilitate effective teaching. Overall, the book aims to inspire a lifelong interest in science and help students understand its significance in their everyday lives.
Oxford International Primary Science 5" is a comprehensive educational resource designed for primary school students, focusing on key scientific concepts and inquiry-based learning. This book aims to foster curiosity and a deeper understanding of the natural world through engaging content and interactive activities. The curriculum is structured around core scientific themes, including life sciences, physical sciences, and Earth sciences, encouraging students to explore topics through hands-on experiments and observations. It emphasizes the development of critical thinking and problem-solving skills, equipping students to ask questions, conduct investigations, and draw conclusions. With colorful illustrations, diagrams, and real-world applications, "Oxford International Primary Science 4" aims to make science accessible and enjoyable. The resource also supports teachers with lesson plans and assessment tools, promoting a collaborative learning environment. Overall, it seeks to inspire a lifelong interest in science and its relevance to everyday life.
Keywords: Earth Sciences; Critical Thinking